Lead Exposure and Motor Development - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The neuromotor assessment of 245 six-year-old urban inner-city children enrolled in the Cincinnati Lead Study is reported from the Departments of Environmental Health and Pediatrics, University of Cincinnati College of Medicine, and the Children's Hospital Medical Center, Cincinnati, OH.